The interaction of ethidium with synthetic double-stranded polynucleotides at low ionic strength. - Baguley, B C (1978)
The interaction of ethidium with synthetic DNA and RNA double-stranded polymers at 0.01 M ionic strength, pH 7.0, has been studied by fluorimetry at low drug to nucleotide ratios. Binding constants have been calculated assuming an excluded-neighbouring site model for the interaction of ethidium with double-stranded polymers. The values obtained are poly d(AT).poly d(AT), 9.5 X 10(6) M-1; poly dA.poly dT, 6.5 X 10(5) M-1; poly d(GC).poly d(GC), 9.9 X 10(6) M-1; poly dG,poly dC, 4.5 X 1-(6) M-1; poly d(AC); poly d(GT), 9.8 X 10(6) M-1; poly d(AG).poly d(CT), 1.3 X 10(6) M-1; poly rA.poly rU, 4.1 X 10(7) M-1. The displacement of ethidium from poly d(AT).poly d(AT) by 9-aminoacridine and an acridine-containing antitumor agent (NSC 156303; 4'-(9-acridinylamino)methanesulphon-m-anisidide) has also been examined.